An overview on philosophical and sociological paradigm to innovation: back to basic / Abdul Majeed Ahmad and Fazliza Che Amat - Ahmad, Abdul Majeed; Che Amat, Fazliza (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Kuhn is an early scholar who pioneered the terms of paradigm and research and its relationship with society. According to Kuhn, paradigm is "... as the entire constellation of beliefs, values, techniques shared by the members of a given community" (Kuhn, 1970, p.175; 2015). A research requires different approaches and methods in accordance with the principles of paradigm differences which do not prevent something that is done to meet the objectives of the research. The differences do not determine which one is right or wrong, but these paradigm differences focus on the comprehensive understanding of the target audience when dealing with research involving societal issues including studies related to innovation.